TESTING AS A FORM OF KNOWLEDGE EXAMINATION OF RUSSIAN MEDICAL TERMINOLOGY - Rozanna Abdullaeva (Zeta Repository, 2023)
The article discusses the methods of applying testing as a form of examination of knowledge of Uzbek-speaking students of medical universities. The organization of the pedagogical process is one of the urgent tasks of modern medical education. Testing as one component of the educational process, ensuring the achievement of its goals and objectives. The forms and methods of testing application are the result of purposeful selection, design and application of content elements, methods, as well as organizational forms of training to achieve certain practical purposes.